If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y(4y + -3) + 15y = 0 Reorder the terms: 6y(-3 + 4y) + 15y = 0 (-3 * 6y + 4y * 6y) + 15y = 0 (-18y + 24y2) + 15y = 0 Reorder the terms: -18y + 15y + 24y2 = 0 Combine like terms: -18y + 15y = -3y -3y + 24y2 = 0 Solving -3y + 24y2 = 0 Solving for variable 'y'. Factor out the Greatest Common Factor (GCF), '3y'. 3y(-1 + 8y) = 0 Ignore the factor 3.Subproblem 1
Set the factor 'y' equal to zero and attempt to solve: Simplifying y = 0 Solving y = 0 Move all terms containing y to the left, all other terms to the right. Simplifying y = 0Subproblem 2
Set the factor '(-1 + 8y)' equal to zero and attempt to solve: Simplifying -1 + 8y = 0 Solving -1 + 8y = 0 Move all terms containing y to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 8y = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 8y = 0 + 1 8y = 0 + 1 Combine like terms: 0 + 1 = 1 8y = 1 Divide each side by '8'. y = 0.125 Simplifying y = 0.125Solution
y = {0, 0.125}
| 15x+5=80 | | 5-2(-3/5)=3(-3/5)+8 | | 4-2(x+5)=9 | | F=1.8(30)+32 | | 3x-6x^2=0 | | 7-x-6x=-28 | | 160=-8(1-3p) | | 7(m-1)-6(m+5)=-37 | | (2x+3y-4z)-(x-y-z)= | | 6y+14=15-9y+14 | | 3(x-7)=8 | | -x-29=-13+2x | | x-9+x=3 | | -x-29=-12x-1 | | 4x^3+20x+10=0 | | y^2-14y=-36 | | 42x+50=1500 | | 2x^2+10x=-15 | | -10=4(x-5)+6x | | 2y+2(y-2)=7y-5(y-10) | | 2x^2+10x=15 | | 70=6x+5x-7 | | 4(-5-5x)=-200 | | 40+273= | | (2y+5)(3y+7)= | | 2(-5+x)=14 | | -8(x+1)+5(3x-4)=6(x-6)+14 | | 10ac*6ab*(-2bc)= | | 6(8+x)=6 | | 2x^2+3x=4 | | 14x+32=70 | | 6x-6-3x=-18 |